Social marketing programs and content analysis of Ivorian online newspaper reporting on breast cancer awareness - Abdoulaye, Ousmane Koffi (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2024)
This article highlights the examination of the true gravity of numerous other malignancies. A public health concern is cancer, especially breast cancer, which is the most prevalent type in women. The content analysis of online newspapers covering breast cancer prevention with social marketing initiatives among Cote d'Ivoire's vulnerable population is reviewed in this study in order to educate and guide the public on the value of early detection. Using a 123-item survey, 307 people from 5 Abidjan municipalities provided the data. To analyse the data, the nonparametric Kruskal-Wallis Test was used. χ2 = 17.005, 6.685, and 11.528, df = 4, p<.05) indicated that social marketing initiatives had an impact on the goods and services.